2016
DOI: 10.1002/da.22487
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Specific Phobia on the Risk of Onset of Mental Disorders: A 10-Year Prospective-Longitudinal Community Study of Adolescents and Young Adults

Abstract: This study provides strong evidence that specific phobia is an early onset disorder predicting the subsequent onset of a range of disorders. Future studies should examine the underlying mechanisms and the potential of using specific phobia as a target for prevention of subsequent psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 37 publications
(77 reference statements)
4
43
0
Order By: Relevance
“…Our study's high prevalence of current specific phobia (6.5%) is consistent with other epidemiological studies on adults [49][50][51]. Although specific phobias tend to have an onset in childhood and to frequently remit into adulthood, recent epidemiological studies reported them as a highly disabling, frequently co-morbid condition in adults warranting therapeutic attention [49] as well as a precursor or even predictor of other mental disorders and, thus, a potential target of preventionespecially when persisting into late adolescence/early adulthood [51][52][53]. Thus, we had included them into our analyses as a condition likely warranting clinical attention.…”
Section: Tablesupporting
confidence: 87%
“…Our study's high prevalence of current specific phobia (6.5%) is consistent with other epidemiological studies on adults [49][50][51]. Although specific phobias tend to have an onset in childhood and to frequently remit into adulthood, recent epidemiological studies reported them as a highly disabling, frequently co-morbid condition in adults warranting therapeutic attention [49] as well as a precursor or even predictor of other mental disorders and, thus, a potential target of preventionespecially when persisting into late adolescence/early adulthood [51][52][53]. Thus, we had included them into our analyses as a condition likely warranting clinical attention.…”
Section: Tablesupporting
confidence: 87%
“…Interestingly, these retrospective studies showed that in the majority of comorbid cases, the onset of specific phobia precedes the other disorder(s) (Magee et al, 1996; Kessler et al, 1996; 1997). Prospective work has shown that specific phobia is associated with a higher odds of later depressive, anxiety and eating disorders (Goodwin et al, 2002; Bittner et al, 2004; Trumpf et al, 2010; Lieb et al, 2016) but not of later substance-use disorders (Zimmermann et al, 2003). Grant et al (2009) showed that specific phobia at baseline was associated with an increased incidence of other anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This large AF illustrates the remarkable potential impact of OCD on subsequent psychopathology among OCD cases. However, considering the PAFs obtained for other factors, for example, specific phobia (Lieb et al., ), OCD seems to be a less likely target for reducing the incidence of specific disorders in universal prevention strategies but a suitable target for selective prevention strategies.…”
Section: Discussionmentioning
confidence: 99%